Who Competes with Whom? The Structure of International Tax Competition - Franz Reiter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Corporate tax rates around the world have considerably decreased in the last decades. While tax competition among countries has been widely accepted as the driving force of this trend, it has remained unclear which countries compete with whom. This paper focuses on country size as a determinant of tax competition. My empirical analysis yields two main results: First, the structure of tax competition is based on a country's size as large countries compete with other large countries and small countries compete with small ones. Second, there is a qualitative di erence as large countries compete worldwide with each other whereas small countries mainly orientate towards geographically close other small states. In an extension I show that tax competition between small countries is particularly strong in Europe.
Keywords: H25; H87; F23; 330